THE INFLUENCE OF THE COMPETENCE OF THESIS SUPERVISOR OF COMMUNICATION SCIENCE UNJ ON STUDENTS' MOTIVATION IN COMPILING THESIS - Sianipar, Ladisa Naftania (Journal of Public Relations and Digital Communication (JPRDC), 2025)
Â This research aims to determine the influence of the competence of thesis supervisors on student motivation in writing theses at the Jakarta State University (UNJ) Communication Science Study Program. The method used in this research is a quantitative approach with survey techniques. Data was collected by distributing questionnaires to 100 students who were in the process of writing their thesis. Data analysis was carried out using simple linear regression to test the influence of supervisory lecturer competence on student motivation. The research results show that there is a significant positive influence between the competence of supervisors and student motivation. The higher the competence of the supervisor, the higher the students' motivation to complete their thesis. The average supervisory lecturer competency score is in the "agree" or "high" category, while student motivation is also in the same category. The results of the analysis of the coefficient of determination show that 90.2% of the variation in student motivation can be explained by the competence of the supervisor, while the remaining 9.8% is influenced by other factors that were not studied. It is hoped that this research can contribute to developing the quality of guidance in the UNJ Communication Studies Program and increase understanding of the importance of the role of supervisors in the thesis preparation process. Therefore, recommendations for increasing lecturer competence and developing a more systematic guidance program are very necessary to support student motivation in writing their theses.